Characterization of the Intact Proteomic Profile of Senescent-Associated Secretory Phenotype by Top-Down Mass Spectrometry - Boroumand, Mozhgan; Dey, Amit; Cupp-Sutton, Kellye; Pierce, Tomas; Tsitsipatis, Dimitrios; Herman, Allison B; Wu, Si; Basisty, Nathan (Analytical chemistry (Washington), 2025)
Cellular senescence is a stable state of cell-cycle arrest characterized by extensive remodeling of the secretome, known as the senescence-associated secretory phenotype (SASP). The SASP profoundly influences tissue microenvironments and contributes to chronic inflammation and age-related diseases. While previous studies have characterized the SASP using bottom-up proteomics, intact proteoforms' diversity and structural complexity remain poorly understood. In this study, we apply quantitative top-down mass spectrometry to profile the intact proteoform composition of the SASP in senescent human fibroblasts, alongside quiescent and proliferating controls. This approach enables direct identification of intact proteoforms with post-translational modifications (PTMs), sequence variants, and isoforms, offering deep insight into the proteomic landscape of senescence. We identify a rich repertoire of previously uncharacterized proteoforms, including variants of HMGA2 with N-terminal acetylation and multiple phosphorylation states (di-, tri-, and tetra-phosphorylated), implicating them as potential senescence biomarkers. Our findings underscore the functional complexity of the SASP and the value of proteoform-level resolution in understanding cellular senescence. This work establishes a robust top-down proteomics strategy for SASP analysis and highlights novel molecular targets for therapeutic strategies aimed at mitigating age-related pathologies.